2012
DOI: 10.1128/aem.00873-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Processing Method on Recovery of Bacteria from Wipes Used in Biological Surface Sampling

Abstract: ABSTRACTEnvironmental sampling for microbiological contaminants is a key component of hygiene monitoring and risk characterization practices utilized across diverse fields of application. However, confidence in surface sampling results, both in the field and in controlled laboratory studies, has been undermined by large variation in sampling performance results. Sources of variation include controlled parameters, such as sampling materials and processing methods, which often di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
4
26
0
Order By: Relevance
“…3). 16,19,32 Another prospective use for this system is examining the antibiotic susceptibility of P. aeruginosa via the electrochemical detection of PYO (Fig. The electrochemical detection of PYO in this potential window also allows for the selective detection of P. aeruginosa from other clinically relevant pathogens (Fig.…”
Section: Electrochemically Monitoring P Aeruginosa Growthmentioning
confidence: 99%
“…3). 16,19,32 Another prospective use for this system is examining the antibiotic susceptibility of P. aeruginosa via the electrochemical detection of PYO (Fig. The electrochemical detection of PYO in this potential window also allows for the selective detection of P. aeruginosa from other clinically relevant pathogens (Fig.…”
Section: Electrochemically Monitoring P Aeruginosa Growthmentioning
confidence: 99%
“…These findings corroborate other studies that reported the relatively small contribution of physical disruption methods to the extraction efficiency of Bacillus cereus vegetative cells (Downey et al . ) and B. anthracis Sterne spores (Da Silva et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Spore suspensions of Bacillus cereus ATCC 10987 were prepared by growing a uniform lawn of spores on solid PGSM [27]. After 7 d of growth (3 d at 37°C and the remainder at 21°C), plates were examined daily for spore formation by removing a small amount of spores and examining with phase microscopy (Olympus AX-70, Olympus America Inc, Center Valley, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Colony forming units (CFU) were enumerated and used to calculate the spore concentration in the working suspension [27].…”
Section: Methodsmentioning
confidence: 99%